2003
DOI: 10.1186/1477-7525-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundTo examine demographic and behavioral associations with self-reported health-related quality of life (HRQOL) among persons with HIV infection or AIDS.MethodsAnalysis of interviews with persons ≥ 18 years of age reported through routine disease surveillance with HIV infection or AIDS to nine state and local health departments from January 1995 through December 1996. Scales were constructed from validated measures of HRQOL, and mean scores were calculated (lower scores signified poorer HRQOL). Measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 30 publications
5
20
1
3
Order By: Relevance
“…It has been demonstrated that patients with higher CD4 counts had better QOL, especially with regard to physical health 42,43,44. Wu et al45 and Ware et al46 also reported similar findings, whereas Paton et al47 found that the differences between the disease stages and correlations with CD4 counts extended to nearly all the subscales of physical and mental health.…”
Section: Effects Of Art On Quality Of Life Of People Living With Hiv mentioning
confidence: 83%
“…It has been demonstrated that patients with higher CD4 counts had better QOL, especially with regard to physical health 42,43,44. Wu et al45 and Ware et al46 also reported similar findings, whereas Paton et al47 found that the differences between the disease stages and correlations with CD4 counts extended to nearly all the subscales of physical and mental health.…”
Section: Effects Of Art On Quality Of Life Of People Living With Hiv mentioning
confidence: 83%
“…Skevington (2012) examined results from eight countries and found across 30 facets of QoL that those aged 40 + had higher QoL and reported eight areas in which they were doing relatively well including positive feelings, safety, home environment, and spirituality, but had poorer energy, sleep, and sex-life. In PLWH, lower HRQOL has been shown to be associated with older age and with lower CD4 counts (Campsmith, Nakashima, & Davidson, 2003). Moreover, physical function decreases more rapidly with age in PLWH compared to uninfected patients (Oursler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The QoL in HIV infection was also compared to the QoL in other chronic diseases [12]. It has been reported that the QoL is related to CD4 + cell counts [13], [14], the onset of symptoms [12], [14], depression and stress [15], [16] and antiretroviral treatment [17].…”
Section: Introductionmentioning
confidence: 99%